Use of rizostar in the production of sorghum silages (Research, Society and Development, 2020)
This study aimed to evaluate the development of culture, mass production, and the silage nutritional value of sorghum under three nutrients fonts. The experiment was conducted as a block randomized design, with three treatments and six replications. The treatments consisted of fonts fertilizations in showing:  Monoammonium Phosphate, with 90.0 kg ha-1, and Rizostar with 37.5 kg ha-1 and 45.0 kg ha-1 doses. The productive parameters of the plants were evaluated at 30 days and at the time of harvesting the plants for silage, in addition to the nutritional value of the silages. The materials presented expressive productions, with averages of 43846; 43346; 44002; and 35674 kg ha-1 of green matter. The Maxisilo sorghum hybrid presented the highest levels of acid detergent fiber (ADF), with a mean of 471.42 g kg-1 dry matter (DM). Crude protein (CP) contents in each hybrid remained constant over time, presenting mean values of 74.37; 65.26; 54.44; 78.43 g kg-1. The mean total digestible nutrients values found in the Dominator sorghum hybrid were 657.34 g kg-1, being higher than the others. After long storage periods, the nutritional parameters of the materials remained stable in their CP, DM, NDF, and ADF values. The aerobic exposure nutritionally deteriorated silages. Fertilization with Rizostar 45, does not influence the final level of plants, fresh raw materials, and dry raw materials, besides significantly increasing the use of samples.